2020
DOI: 10.1140/epjc/s10052-020-7738-8
|View full text |Cite
|
Sign up to set email alerts
|

Karmarkar scalar condition

Abstract: In this work we present the Karmarkar condition in terms of the structure scalars obtained from the orthogonal decomposition of the Riemann tensor. This the new expression becomes an algebraic relation among the physical variables, and not a differential equation between the metric coefficients. By using the Karmarkar scalar condition we implement a method to obtain all possible embedding class I static spherical solutions, provided the energy density profile is given. We also analyse the dynamic adiabatic cas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 37 publications
1
39
0
Order By: Relevance
“…the (2.58)-(2.59) reduce to those obtained here using anisotropy together with the Karmarkar condition. Thus, although we had chosen ∆ for the mathematical simplicity, the results obtained are physically significant and in agreement with those obtained in [25].…”
Section: Fluid Distribution and Field Equationssupporting
confidence: 78%
See 1 more Smart Citation
“…the (2.58)-(2.59) reduce to those obtained here using anisotropy together with the Karmarkar condition. Thus, although we had chosen ∆ for the mathematical simplicity, the results obtained are physically significant and in agreement with those obtained in [25].…”
Section: Fluid Distribution and Field Equationssupporting
confidence: 78%
“…Recently, the Karmarkar scalar condition has been used for the nonstatic system, where they found two class of solutions [25]. One of their solutions is that of a horizon free radiating collapse For the collapsing phenomena Θ should be negative throughout the collapse which is confirmed from the figure that as the collapse starts at t = −100, Θ has zero value and it starts decreasing till the collapse reaches its end state at t = 0.…”
Section: Fluid Distribution and Field Equationsmentioning
confidence: 87%
“…Both electric charge q(r) and electric field E(r) must be strictly positive and increasing functions with radius, meaning that at the origin both must be null ı.e, q(0) = E(0) = 0. From expressions (35) and (37) the electric field is given by…”
Section: B Electric Propertiesmentioning
confidence: 99%
“…In [57], it has been shown that for the static case, Karmarkar condition together with the pressure isotropy yields the Schwarzschild [72] like form of the metric functions. Also, it has been shown that these set of gravitational potentials are the special class of those found in [73]. Thus, although we have assume this particular form of (36) for the mathematical simplicity, represents the physically viable solutions.…”
Section: Field Equations and Matching Conditionsmentioning
confidence: 94%